Določitev meje na morju med Republiko Hrvaško ter Republiko Bosno in Hercegovino - Grbec, Mitja (Pravnik, 2013)
The particular position of the coastline of Bosnia Herzegovina and its waters is interesting not only in the context of the Adriatic and Mediterranean Sea, but worldwide. The reason lies in the (geographical) fact that Bosnia and Herzegovina exercises sovereignty over a narrow strip of territory called the Klek-Neum Corridor enclosed between two parts of the Croatian coastline and in the (legal) fact that the maritime areas of Bosnia Herzegovina were both on the basis of the 1994 and 2004 Croatian Maritime Code closed within the Croatian system of straight baselines. This paper tries to discuss some legal issues which have arisen in relation to the specific maritime status of Bosnia and Herzegovina. In addition to the sole (maritime) delimitation (e.g. the in 1999 signed Border Treaty between Croatia and Bosnia and Her-zegovina), there are at least three other aspects which are interesting from the standpoint of the contemporary law of the sea. The first is the legal status of the waters of Bosnia and Herzegovina, the second is the legality of the Croatian enclosure of the maritime zones of Bosnia and Herzegovina into its system of straight baselines while the third is the right of navigation of Bosnia and Herzegovina through Croatian (internal) waters to the high seas (potential EEZs). In the light of the ongoing arbitration proceeding between the Republic of Slovenia and the Republic of Croatia (land & maritime boundary), it seems important that the border treaty signed in 1999 between Croatia and Bosnia and Herzegovina makes reference to the application of the principle of uti possidetis without differentiating between its application on land and/or sea.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; Croatia; državne meje; Hrvaška; morje; pomorsko pravo; sea